Directions of using pedagogical technologies in mastering business and entrepreneurship subjects of higher education students - Karimova, Maftuna; Khakimov, Sherzod; Khimmatov, Mekhroj (MMIT Proceedings, 2024)
This article briefly describes some modern, interactive pedagogical methods for higher education students to increase their interest in business and entrepreneurship.